Effects of Overconfidence Bias, Loss Aversion, and Herding on University Students’ Investment Decisions in Surabaya - Maria Yovita R. Pandin; Feriona Ayurizta Iliyas; Amalia Tizka Zhahrina; Aim Matus Noer Solehah (Economy and Finance Enthusiastic, 2025)
This study investigates the effects of overconfidence bias, loss aversion, and herding behavior on university students’ investment decisions in Surabaya. Using a quantitative approach, data were collected via an online questionnaire (Google Form) distributed to students from state and private universities, yielding 102 valid responses. The population frame referred to the 34,464 students in Surabaya, and the minimum sample size was determined using the Isaac and Michael formula. Each construct was measured with 10 indicators, all of which passed validity (r count > r table, Sig. < 0.05) and reliability tests (Cronbach’s Alpha > 0.60). Data were analyzed using multiple linear regression with SPSS, preceded by classical assumption tests (normality and multicollinearity), which indicated that the model was appropriate. The results show that overconfidence bias, loss aversion, and herding behavior each have a significant partial effect on investment decisions, as evidenced by t-count values of 8.176, 65.159, and 8.822 respectively, all greater than t-table (1.984) with significance levels of 0.000. Simultaneously, the three psychological factors also have a significant joint influence on investment decisions (Sig. 0.012 < 0.05). These findings confirm that behavioral biases play a crucial role in shaping students’ investment behavior, implying the need to strengthen financial education and awareness of psychological biases among young investors.